Influence of Polyethylene Glycol on the Properties of TiO2Films by Squeegee Method - Malek, M.F.; Ismail, A.S.; Yusoff, M.M.; Mohamed, R.; Ahmad, M.K.; Rusop, M. (EDUCATUM Journal of Science, Mathematics and Technology, 2016)
An extremely easy method is presented for producing TiO2 nanoparticles (NPs) films as photoanode in dye-sensitized solar cell applications. This paper presents the study on the effect of Polyethylene glycol 20000 (PEG 20000) on the properties of TiO2 NPs films. The amount of PEG 20000 were varied between 0.1 and 0.5 g. Sonication and stirring of commercial TiO2 NPs Degussa P25 and PEG 20000 in ethanol results in highly homogeneous dispersions which are used to prepare TiO2 films. The use of optimum amount of PEG 20000 will increase the light absorption due to the increment of the surface area within the film. The films were characterised using ultraviolet-visible-near infrared spectrometer, field emission scanning electron microscopy and current-voltage measurement.